Education and childhood in some writings of Walter Benjamin - Schlesener, Anita Helena (Paidéia (Ribeirão Preto), 2011)
This work intends to reflect about some writings of Walter Benjamin about education and childhood, contained in Berliner Kindheit um Neunzehnhundert. Benjamin place in question the education bourgeois and theirs practices and reflect about children's imaginary. Joining perception and concept, Benjamin present concepts that insert education in the context of one philosophy ok history. This article aims at accentuate the originality of a writer that, in context of the European society from 1920 to his death by suicide on 1940, placed importants questions about education and suggested news paradigms of interpretation, accordant Benjamin's affirmation, method of montage, how a mosaic or a constellation.